PEMANFAATAN BIAYA PEMASARAN UNTUK PENINGKATAN EFISIENSI, EFEKTIVITAS DAN PRODUKTIVITAS BERBASIS DEA - Sinurat , Erna Anjelina; Siahaan, Yetty Deliani; Saribu, Ardin Dolok; Pardosi, Ririn Wantika; Manurung, Valentina; Ompusunggu, Joel Pardomuan; Saragi, Kurnya Suparto; Zai, Putri Five; Juliani Silitonga, Cristin Erni (Jurnal Akuntansi Kompetif, 2024)
The Triangel Service conceptual model shows a close relationship between efficiency, effectiveness and marketing costs.DEA (Data Envelopment Analysis) method: DEA is proven effective in measuring the level of efficiency and effectiveness, providing an exact value for comparison between DMUs (Decision Making Units). Data Envelopment Analysis (DEA) is used to analyze effectiveness, efficiency, and productivity.1. The weakness in the main journal is the lack of focus on marketing cost allocation although DEA can measure efficiency and effectiveness, the analysis lacks depth in assessing the impact of marketing cost allocation on productivity. The main journal also has limitations in providing suggestions for improvements to the research results, which makes the results of the operation not run efficiently.